On Roman brick stamps ans the Latin –(a)es genitive - Tommi Alho; Ville Leppänen (Pallas, 2017)
The origin of the first declension genitive singular ending -(a)es for -ae in Latin inscriptions has been often discussed and variously explained. Based on brick stamp data, we confirm the view that the ending represents a Latinisation of the Greek morpheme -ης. We argue, however, based on the normative nature of language, that it was conventionalized as a permanent transfer from early on, and that the occurrences of the ending in first and second century inscriptions do not represent instances of code-switching. In other words, by the second century AD at the latest, the use of the ending was conventional, i.e. it had become a norm, in certain linguistic communities.